Detection Levels of Cytokines (IL-6 and IL-18) and Microbial Parameters in Patients with Renal Failure in Diyala Province - Wasan A. Wahab Alsiadi; Alaa Mohammed Albayati; Ban Talib Elhaboby (Indian Journal of Forensic Medicine & Toxicology, 2021)
Current study was conducted in Diyala province for kidney failure patients ( Ibn Sina Center ) for dialysisin Baqubah teaching hospital and started from beginning August 2016 to end April 2017. A total 100 bloodsample had from kidney failure patients, has been the number males 61 and females 39 with age range (10– 88) years and collected 50 of blood sample from oculary healthy individuals act as a control group , hasbeen the number males 25 and females 25 with age range 10 – 88 years . By (ELISA) technique detectionimmunological parameters (IL-6 , IL-18) , and (SRID) for detection microbial parameters (HBV, CMV , T.gondii, HCV) . Result of study expressed that the incidence of disease rate among males 61% more thanfemales 39% with no significant different (P>0.05), also highest rate disease in both age groups (31-50, 51-70) years , while lowest rate disease the age range (10-30 , >70) years recorded with significance different)P <0.05(. So, high levels of ( IL-18) for patients than to control with significance different between studygroups (P <0.05), while (IL-6) was raised in patients compared to control. Also, result showed positivity of( HBV, CMV , T. gondii, HCV ) in patients was (8% , 13%, 10%, 25% ) respectively with high significantdifferent (P<0.05). Conclusions of current study showed male more than female, age period >70 and 51-17year recorded highest percentage infection ,high levels of immunological (IL-6 and IL-18) in renal dialysispatients, as well as to some microbial infected patients with kidney failure. The aim of study is detectionlevels of cytokines (IL-6 and IL-18) and some microbial infection in patients with renal failure.